Cell-substrate adhesion during Trypanosoma cruzi differentiation (The Rockefeller University Press, 1988)
The transformation of Trypanosoma cruzi epimastigotes to the mammal infective metacyclic trypomastigotes (metacyclogenesis) can be performed in vitro under chemically defined conditions. Under these conditions, differentiating epimastigotes adhere to a surface before their transformation into metacyclic trypomastigotes. Scanning and transmission electron microscopy of adhered and non-adhered parasites during the metacyclogenesis process show that only epimastigotes and few transition forms are found in the first population, whereas metacyclic trypomastigotes are exclusively found in the cell culture supernatant. PAGE analysis of the [35S]methionine metabolic labeling products of adhered and non-adhered parasites shows that although most of the polypeptides are conserved, adhered parasites express specifically four polypeptides in the range of 45-50 kD with an isoelectric point of 4.8. These proteins might be involved in the adhesion process and are recognized by an antiserum against total adhered parasite proteins. This antiserum also recognized a group of 45- 50 kD in the iodine-radiolabeled surface proteins of differentiating cells, providing direct evidence that these components are indeed surface antigens. The results suggest that epimastigotes must adhere to a substrate before their transformation to metacyclic trypomastigotes, being released to the medium as the metacyclogenesis process is accomplished. This could correspond to the process naturally occurring within the triatomine invertebrate host.